Síntese in situ pelo método Pechini assistido por micro-ondas dos compósitos livres de chumbo (1-x)BaZr0,08Ti0,92O3/(x)CoFe2O4 - Caminata, Laís Pacheco (2019)
Currently, there is considerable interest in developing lead-free composites in the scientific area. This is occurs due to the growing demand for new multifunctional materials with potential technological applications. Thus, there is also a need to improve the methods to obtain these materials to achieve the desired properties and optimization of the subsequent processing steps. Considering this, the purpose of this study is the synthesis via in situ by microwave assisted Pechini method of biphasic lead-free composites of the system (1-x)BaZr0,08Ti0,92O3/(x)CoFe2O4, with several molar ratios of the CFO phase. Microwave energy was used for heating only in solvent evaporation and polymeric resins formation steps. The microwave assisted Pechini method provided a significant reduction in the duration and in the temperatures used in the evaporation of the solvents and formation of the resins steps. Thus, a lower energy expenditure in the procedures was promoted. Furthermore, the methodology proposed resulted in obtaining BZT nanopowders with a high degree of crystallinity and a decrease in the temperatures and energies required for crystallization. While for lead-free biphasic composites (1-x)BZT/(x)CFO, 0.10≤x≤0.50, the synthesis in situ obtained both constituent phases of the system in only one stage of heat treatment, also reaching a highly homogeneous distribution of the phases with average sizes of particles on a nanometric scale. Using microwave heating in the in situ synthesis of the composites favored the decrease of the crystallization temperatures of both phases, as well as lower particle sizes for the BZT phase. All the nanopowders of the lead-free biphasic composites (1-x)BZT/(x)CFO, 0.10≤x≤0.50, synthesized by the microwave assisted Pechini method presented ferrimagnetic behavior. In general, it is inferred that the protocol established for the in situ synthesis by the microwave assisted Pechini method showed to be reproducible, ensuring its viability to obtain lead-free biphasic systems.